Green Management in Hotels: A Supply-Side Analysis - MBASERA, Miriam; du PLESSIS, Engelina; SAAYMAN, Melville; KRUGER, Martinette (Journal of Environmental Management and Tourism; Vol 7 No 2 (2016): JEMT Volume VII, Issue 2(14) Summer 2016, 2016)
Tourism is one of the largest industries in the world and an important economic tool. However, it also has many negative effects on the environment. Hotels, as part of the tourism industry, have a significant impact on the environment and it is therefore imperative that they should take action to mitigate these impacts. This increased awareness and sensitivity demands from hotel managers to become “greener” in their daily work. The goal of the research was to examine managers’ perceptions of green management in hotels in South Africa and Zimbabwe and to establish how green management affects hotel performance. A qualitative research was carried out in eight hotels in the above-mentioned countries, employing the case-study approach. Some managers do not fully understand the concept of green management. To some extent, this indicates that there exists a gap between managers’ knowledge and what green management means. This implies that training should constitute a significant part of hotels’ activities so that hoteliers may consider green management in their daily operations. The results could help hotel managers in the identification of staff training needs so that they may have a clear understanding of green management, enabling them to participate fully in green management activities.
Keywords: Hotels; green management; environmentally friendly; South Africa; Zimbabwe